GPTheatre Seen from the Stage: an (intra-human) dialogue with dramaturgs Giulia Asselta and Maddalena Mazzocut-Mis and director Paolo Bignamini (Itinera, 2025)
The interview presents the GPTheatre project “as seen from the stage”, through the experience of the theatre director and the dramaturgs who found themselves involved in this unusual experiment.